Design and analysis of a one-piece variable stiffness device - Yong, Patrick Weng Hong. (2013)
Stiffness is a property that is inherent in all materials and structures, and it is able to allow a structure to resist permanent deformation up to a certain point before succumbing to the force acting upon the structure. However, stiffness is found to have a linear relationship with the amount of force used. There the purpose of this project is to explore conceptual ideas of a various stiffness device that is made up of a single construct, using flexure joints to obtain its non-linear stiffness characteristics. Data gathered via a simulation programme will be compared and analyzed. A literature review on the robots, degrees of freedoms and the properties of flexure hinges will be discussed